Hydrophobic tail length in spin crossover active iron(ii) complexes predictably tunes T½ in solution and enables surface immobilisation. Issue 10 (21st April 2020) - Sundaresan, Sriram; Kitchen, Jonathan A.; Brooker, Sally
Abstract : Linear correlation of the hydrophobic alkyl tail length R employed in [Fe II (L H-OR )(NCBH3 )2 ] with the spin crossover switching temperature is a very convenient method of predictably tuning the iron(ii ) spin state. Abstract : The literature tetradentate acyclic Schiff base ligand HL H-OH (from the 2 : 1 reaction of pyridine-2-carboxylaldehyde with 1, 3-diamino-2-propanol) was alkylated using a range of 1-bromoalkanes varying in length, BrR (R = C10 H21, C16 H33, C18 H37, C20 H41 and C22 H45 ) to yield five new ligands, L H-OR . The synthesis, magnetic and Langmuir characteristics of the corresponding family of six neutral mononuclear Fe(ii ) complexes, the parent complex [Fe II (HL H-OH )(NCBH3 )2 ] and the five alkylated ligand derivatives [Fe II (L H-OR )(NCBH3 )2 ], is detailed. The solution spin crossover temperature, T ½, can be tuned by two methods: (a) increasing the solvent polarity index ( P ′) from 5 to 7 increases T ½ by 172 K, whereas (b) increasing the tail length from C10 to C22 decreases T ½ by 115 K. In both cases strong linear correlations are observed, so both of these, choice of solvent ( R 2 = 0.99, albeit only for three solvents) and of tail length ( R 2 = 0.98, for five complexes), are levers for the predictable tuning of the spin state in advance of synthesis. The compounds with longer tails, C18, C20 and C22, showed a small window of thermal hysteresis (<5 K) in D3 -acetonitrile solution. Water solubility hampered the formation of Langmuir films of these complexes. But the use of a 1 : 1 mixture of stearic acid with [Fe II (L H-OC18 )(NCBH3 )2 ] facilitated the formation of a stable Langmuir film, a monolayer of which was transferred onto a quartz slide: multi-layering was not possible.